A service failure framework of hotels in Taiwan: Adaptation of 7Ps marketing mix elements. (January 2018) - Loo, Poh Theng; Leung, Rosanna
This study aims to identify and categorize service failures from luxury hotels in Taiwan. A theoretical framework is proposed by adapting marketing mix elements. A total of 411 negative comments were found and extracted from four popular online review websites from 20 luxury hotels in Taipei. The content analysis method was employed for data analysis. The study results show that majority of luxury hotels in Taiwan encounter critical product issues, especially concerning the condition of facilities and equipment offered in the guest rooms. Furthermore, cleanliness of the hotel rooms requires greater attention, especially the cleanliness of room carpets, which could affect the hotel guests' comfort during their stay. The findings and recommendations can provide luxury hotel practitioners in Taiwan a clearer picture about the service problems faced and enable them to conduct further investigations for further improvements. So far, existing studies are lacking of a systematic framework in demonstrating the service failures from online reviews. This research attempts to fill this gap.